An algorithm for one - dimensional tidal model of river networks - Dac, Nguyen Tat (Vietnam Journal of Mechanics, 1983)
There has been a great number and variety of numerical techniques for one-dimensional tidal model of river networks, e.g. [1. 2], which base themselves on the integration of the Saint-Venant equation. [1] requires a complicated procedure in classification of branches and in computation of the recurrence coefficients. [2] has some advantage in comparison with [1] but the degree of the system of linear equation to be solved is quite great. This makes it [l] fit only for simple networks of river. In this report a modified algorithm for river networks is given. It is shown that there is only one recurrence relation to be used for all branches describing the networks the graph structure is formed. The algorithm is flexible for users. The theory presented in this report has been programmed in FORTRAN IV and the resulting computer program has been tested on a part of Mekong river.